Standardization of shelf-stable aonla, carambola, papaya, pineapple, and watermelon rind candies (Bangladesh Journal of Agricultural Research, 2008)
This study was conducted to standardize procedures for preparing candies from aonla, carambola, papaya, pineapple, and watermelon rind. Fruit's slices were treated with preservative and firming agents, pricked, blanched, and then processed. Initially the range of moisture content of candies was 15.6 to 16.15%, total sugar 79.78 to 81.63%, reducing sugar 55,56 to 58.71%, and acidity 0.54 to 0.88%. The candies were tasted by a taste-testing panel for different sensory attributes using 9 point Hedonic scale. During four months of storage, the results showed that aonla and carambola candy packed in high density foil pack (HDFP) secured the highest sensory score, while papaya, pineapple, and water melon rind candy packed in normal polyethylene pack (NPP) showed the lowes sensory acceptability.Bangladesh J. Agril. Res. 32(4) : 621-628